2003
DOI: 10.1007/s100720300004
|View full text |Cite
|
Sign up to set email alerts
|

Italian version of the Epworth sleepiness scale: external validity

Abstract: We assessed the validity of an Italian language version of the Epworth sleepiness scale (ESS). The translated ESS was compared to the multiple sleep latency test (MSLT), considered the gold standard for the diagnosis of excessive daytime sleepiness (EDS). Within the context of a multicentric national study on narcolepsy (Gruppo Italiano Narcolessia Studio Epidemiologico Nazionale, GINSEN) involving 17 Italian sleep centres, we compared the two diagnostic tests on 91 prospectively recruited subjects with suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(207 citation statements)
references
References 17 publications
2
200
1
4
Order By: Relevance
“…Regarding treatment type, we found in this study that clinical insomnia was the most associated with chemotherapy (62%), this result agrees with the findings of the literature [9,22]. Berger and Fair reported that women undergoing chemotherapy for breast cancer who had more objectively measured daytime sleep and nighttime awakenings reported more chemotherapyrelated fatigue [23]. Sleepiness in cancer patients has seldom been studied, it's often evaluated as clinical manifestation of fatigue.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding treatment type, we found in this study that clinical insomnia was the most associated with chemotherapy (62%), this result agrees with the findings of the literature [9,22]. Berger and Fair reported that women undergoing chemotherapy for breast cancer who had more objectively measured daytime sleep and nighttime awakenings reported more chemotherapyrelated fatigue [23]. Sleepiness in cancer patients has seldom been studied, it's often evaluated as clinical manifestation of fatigue.…”
Section: Discussionsupporting
confidence: 82%
“…12,13 Patients and controls provided informed consent, which was approved by the Independent Ethical Committee of the University Hospital of Rome "Tor Vergata".…”
mentioning
confidence: 99%
“…At diagnosis and at each follow-up we measured the Epworth Sleepiness Scale score. 24 At each follow-up visit we calculated the retention rate (calculated as the number of subjects who returned for follow-up divided by the total number of subjects) and downloaded the CPAP use data from the CPAP device. Any problems with CPAP treatment were addressed, and the CPAP data were reviewed with the subject, without emphasizing the achievements.…”
Section: Methodsmentioning
confidence: 99%